Financial access and exclusion in Kenya and Uganda - Susan Johnson; Max Ni\~no-Zarazua (University of Bath, Centre for Development Studies (CDS), 2009)
Policy emphasis has recently shifted to 'Finance for All' given evidence that financial sector development (FSD) contributes to growth but that the primary effects on poverty do not arise from pro-poor provision. This paper uses data from Financial Access Surveys carried out in 2006 in Kenya and Uganda to investigate the socio-economic, demographic and geographical factors causing access to and exclusion from formal, semi-formal and informal financial services. It approaches this from the perspective of institutional analysis. It finds, first, that social institutions do present underlying barriers to access - more so than geography - and that informal provision is extensive. These findings suggest that institutional theories of FSD need to address the role of underlying social institutions and better understand the role of informal finance, and that policy for effective outreach must similarly consider these dimensions.
Keywords: 330; financial access; financial exclusion; microfinance; social institutions; informal finance